Du documentaire à la fiction : Tierra Caliente (2004) et El violín (2005), deux modalités d’approche de la réalité mexicaine par Francisco Vargas - Julie Amiot-Guillouet (Caravelle)
In the context of a renewal of Latin-American films since 1990, Mexican cinema is an exception and seems to be going through a long crisis from which only the documentary manages to escape. The documentary’s difficulty consists in its diffusion, mostly confidential, which prevents it from reaching a wide audience. The edition of a documentary and a work of fiction by Francisco Vargas in the same DVD, proposes a solution to this problem by managing to question once more the relations between documentary and fiction ; fiction’s success offers the possibility for the documentary to be seen, especially because two films suggest two complementary looks upon a reality which the film-producer wants to denounce through his works.